PHYTOCHEMICAL SCREENING AND EVALUATION OF ANTIMICROBIAL ACTIVITY, ANTIOXIDANT ACTIVITY, ANTICOAGULANT ACTIVITY AND FIBRINOLYTIC ACTIVITY OF LEAVES OF ANDROGRAPHIS PANICULATA(LEAF) - LALITHA.G; DR.T.H.NAZEEMA; SHARMILA.L (International Journal of Pharma and Bio Sciences, 2015)
Medicinal plant based drugs have an added advantage of being simple, effective and offering a broad spectrum of activity with greater emphasis on preventive action. They contain active constituents that are efficient in the treatment of many human diseases. The present study was an attempt to assess few antibacterial, antioxidant, anticoagulant and fibrinolytic activity of Andrographis paniculata. The phytochemical screening of A. Paniculata (leaf) revealed the presence of flavanoids, glycosides, saponins, phenols, tannins and steroids. The plant part (leaf) exhibited antibacterial and antioxidant activities that varied from solvent to solvent. The study also revealed that ethanolic extract exhibited significant antimicrobial activity, whereas the methanolic extract exhibited antioxidant activities compared to other organic solvents and aqueous extracts. The aqueous extract exhibited significant anticoagulant activity compared to ethanol and methanol extract.In fibrinolytic activity, the ethanol and methanol extract exhibited significance result whereas in aqueous extract there was no fibrinolytic activity.